Pemarasitan Benalu Dendrophthoe pentandra (L.) Miq. pada Tanaman Koleksi Kebun Raya Cibodas, Jawa Barat - Sunaryo, Sunaryo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2008)
The mistletoes of Dendrophthoe pentandra (Loranthaceae) grow as parasite on several plant collections of CibodasBotanical Gardens. Plant collections which attacked by mistletoe are Ficus type (Moraceae), and by individual innumber at most is Syzygium racemosum (Myrtaceae). 299 infected and uninfected branches of 67 host specieswere observed. The results showed that the host branches can be destroyed by mistletoe. Moreover, in the naturalconditions, the mistletoe causes degraded of the distal part of the infected branches.